EMOTIONAL INTELLIGENCE AND DECISION-MAKING IN FINANCIAL SCAMS. (11th November 2018) - Mueller, E; Wood, S; Klapatch, L; Paul, J; Reed, C; Xi, P
Abstract: Financial scams are an insidious problem for consumers. Older adults have been portrayed as being particularly vulnerable to financial scams. However, results have been inconsistent regarding whether older adults are more vulnerable to fraud than younger adults. Two goals of the current study were to investigate the claim that there is an age-related vulnerability to scams and to examine whether Emotional Intelligence (EI) may be associated with scam susceptibility. Participants (N = 154) between the ages of 18 and 80 were recruited via Amazon's Mechanical Turk and completed measures of EI, Decision-Making, and Scam Susceptibility. The "younger" group (M = 8.86, SD = 1.19) reported higher Susceptibility to Persuasion than did the "older" group (M = 8.49, SD = 0.99); t(152) = -2.12, p = 0.036. However, the "older" group (M = 4.69, SD = 0.67) found the fraudulent investment pitches significantly more appealing than did the "younger" group (M = 4.39, SD = 0.75); t(152) = 2.64, p = 0.009. Additionally, participants with higher EI generally rated fraudulent investment pitches as more appealing (r = 0.247, p = 0.002). The results of this study suggest that while younger adults may be more susceptible to persuasion, older adults still find fraudulent advertisements more appealing. Previous research suggests that individuals with higher EI are actually worse at detecting deceit in others (Baker, ten Brinke, & Porter, 2013). Because the "older" group scored higher on EI, this provides a possible explanation for why the "older" group found the fraudulent advertisements more appealing.